Chile : Staff Report for the 2015 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2015)
This 2015 Article IV Consultation highlights that the GDP growth of Chile has remained lackluster over the past year. The main force behind the economic slowdown in 2014 has been the sharp fall in private investment, mainly the consequence of the end of the mining boom, but also reflecting the uncertainty and adjustment costs associated with the structural reform agenda. The IMF staff expects growth to increase modestly to 2.5 percent in 2015, mainly thanks to strong fiscal support. Private domestic demand should strengthen somewhat in 2016, primarily as very simulative monetary conditions and a gradual recovery of business confidence sustain private investment.